OUTPUT DAN DAMPAK PELATIHAN PENGEMBANGAN PENILAIAN PROJEK DAN INSTRUMENNYA DALAM PEMBELAJARAN MATEMATIKA - Rahayu, Wardani; Permana, Agus Agung; Sulaeman, Erwin; Noviah, Ema; Kismanto, Nugro (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Students are expected to be able to improve their creative thinking, critical thinking and problem solving, communication, and collaboration skills in learning mathematics. To achieve this goal, teachers must have the skills to apply Higher Order Thinking Skill (HOTs)-based learning models with authentic assessment techniques. One of the authentic assessment techniques is project assessment. This community service aims to help teachers in the Caianjur Region have the ability to develop project tasks and their assessment instruments in mathematics lessons. The training participants were 27 elementary school teachers. The training was carried out by providing the concept of project assessment, developing project assessment instruments and practice by applying cooperative learning models. At the end of the training, a self-assessment was carried out to measure the ability to understand the training material, training activities and follow-up of training results in elementary schools where teachers teach. The results of this training show that training participants can know how to apply project assessment in the learning process in mathematics subjects, develop project assignments in mathematics lessons, and are able to share knowledge with peers. Abstrak Siswa diharapkan mampu meningkat kemampuan creative thinking, critical thinking and problem solving, communication, dan collaboration dalam pembelajaran matematika. Untuk mencapai tujuan ini maka guru harus memiliki keterampilan menerapkan model pembelajaran berbasis Higher Order Thinking Skill (HOTs) dengan teknik penilaian autentik. Salah teknik penilaian autentik adalah penilaian projek. Pengabdian pada Masyarakat ini bertujuan untuk membantu guru di Wilayah Caianjur memiliki kemampuan pengembangan tugas projek dan instrumen penilainnya pada pelajaran matematika. Peserta pelatihan sebanyak 27 orang guru sekolah dasar. Pelatihan dilaksanakan dengan pemberian konsep penilaian projek, pengembangan intrumen penilaian projek dan praktik dengan menerapkan model pembelajaran kooperatif. Diakhir pelatihan dilaksanakan self assessment untuk mengukur kemampuan pemahaman materi pelatihan, aktivitas pelatihan dan tindaklanjut hasil pelatihan di sekolah dasar tempat guru mengajar. Hasil pelatihan ini menunjukkan peserta pelatihan dapat mengetahui cara menerapkan penilaian projek dalam proses pembelajaran pada mata pelajaran matematika, mengembangkan tugas projek pelajaran matematika, dan mampu berbagi pengetahuan kepada teman sejawat.